The Prevalence of Self-Reported Systemic Allergic Reaction to Hymenoptera Venom in Beekeepers Worldwide: A Systematic Literature Review and Meta-Analysis - Carli Tanja; Locatelli Igor; Košnik Mitja; Kukec Andreja (Sciendo, 2024)
Beekeepers represent a high-allergic risk population group due to their unavoidable seasonal or persistent exposure to the elicitors of Hymenoptera venom allergy, bees in particular. A systematic literature review and meta-analysis aimed to estimate the prevalence of self-reported systemic allergic reaction to Hymenoptera venom among beekeepers worldwide.